2000
DOI: 10.1034/j.1600-065x.2000.017510.x
|View full text |Cite
|
Sign up to set email alerts
|

Repertoire selection by pre-B-cell receptors and B-cell receptors, and genetic control of B-cell development from immature to mature B cells

Abstract: During B-cell development the surrogate light (SL) chain is selectively expressed in progenitor and precursor B cells during the developmental stages of D(H) to J(H) and V(H) to D(H)J(H) rearrangements. Approximately half of all muH chains produced by these rearrangements cannot pair with SL chains and cannot form a pre-B-cell receptor (pre-BCR). A spectrum of affinities between VpreB and individual V(H) domains generates preB cells with pre-BCR of different fitness which, in turn, determines the extent of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 0 publications
1
116
0
1
Order By: Relevance
“…Cells that have undergone a successful V to D-J recombination are selected, and the expression of the pre-BCR mediates their proliferative expansion [1,4,12,13,[25][26][27][28]. In mice lacking the surrogate light chain components, and thus unable to express the pre-BCR, this selection and expansion process fails to operate, resulting in the generation of fewer immature and mature B cells [1,[12][13][14]29]. Nevertheless, serum antibodies are at normal levels, and moreover, these mice are able to mount T-cell-dependent and -independent humoral immune responses [29].…”
Section: Tolerance Checkpoints In B-cell Development Large Pre-bii Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells that have undergone a successful V to D-J recombination are selected, and the expression of the pre-BCR mediates their proliferative expansion [1,4,12,13,[25][26][27][28]. In mice lacking the surrogate light chain components, and thus unable to express the pre-BCR, this selection and expansion process fails to operate, resulting in the generation of fewer immature and mature B cells [1,[12][13][14]29]. Nevertheless, serum antibodies are at normal levels, and moreover, these mice are able to mount T-cell-dependent and -independent humoral immune responses [29].…”
Section: Tolerance Checkpoints In B-cell Development Large Pre-bii Cellsmentioning
confidence: 99%
“…At this stage of differentiation, the IgH chain loci are V to D-J rearranged and those that have done this successfully (synthesized a m-heavy (mH) chain) are positively selected within this compartment. This positive selection is mediated by the pre-BCR, which is composed of the mH chain and the surrogate light chain proteins Vpre-B and l5 [10][11][12][13][14][15]. Moreover, the pre-BCR induces a strong proliferation of these positively selected pre-B cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and R. Haire, unpublished observations). Using a V-region-directed cloning technique in lamprey lymphocytes, a single gene was identified that resembles VpreB, which encodes a surrogate BCR light-chain component that is expressed early in lymphocyte ontogeny in higher vertebrates but does not participate directly in the function of the mature BCR 92 . The lamprey VpreB-like molecule might reflect the character of an early common ancestor that might or might not have mediated an immune function 93 .…”
Section: Anticipatory Immunity In Jawless Vertebratesmentioning
confidence: 99%
“…26,27 Following successful antigen receptor rearrangement, signals from the pre-T-cell receptors (pre-TCRs) or pre-B-cell receptors (preBCRs) signal the lymphocytes to promote the survival of the progenitors and induce their further differentiation. 28,29 T-lymphocyte progenitors that express a functional receptor are further subjected to both positive and negative selection to ensure that a functional receptor exists while eliminating those cells with self-reactive antigen receptors, which could be dangerous due to the potential for autoimmunity ( Figure 3). 30 When the avidity of interaction of the TCR and endogenous major histocompatibility complex (MHC) molecules is low, T-cell progenitors fail to be positively selected and undergo apoptosis.…”
Section: The Bcl-2 Familymentioning
confidence: 99%